Updating the breeding sites of Aedes aegypti (Diptera: Culicidae) in Camagüey, Cuba - Diéguez-Fernàndez, Lorenzo; Alarcón-Elbal, Pedro María; Pino-Bacardi, Rafael; Fimia-Duarte, Rigoberto; Osés-Rodríguez, Ricardo; Iannacone, José; Varona-García, Francisco; Navarro-Vegas, Néstor (InterAmerican Journal of Medicine and Health, 2024)
Mosquito-borne diseases continue to be of significant public health concern in various parts of the world, facilitated by the adaptations that certain species, such as Aedes aegypti, have managed to develop. In order to update the bioecological knowledge of A. aegypti populations in a Health Area of Camagüey Province, Cuba, a comprehensive entomological survey was conducted both indoors and outdoors, covering the entire urban population, encompassing a total of 36,584 households. Aedes aegypti colonized 52 types of breeding sites, of which 15 were found to be permanent and suitable (29.0%), contributing 82.0% of the positivity. Low tanks were particularly prominent (43.0%). Positivity in natural breeding sites remained low (0.11%). Larvae were collected in habitats with high levels of eutrophication (17.30%), grouped in 28 positive breeding sites, accounting for 3.32% of the total number of positive sites. No differences were observed in the total number of positive breeding sites and capture locations between climatic seasons, indicating a consistent pattern of positivity throughout the study year, during which six types of breeding sites exceeded a 70% monthly repetitiveness. These results underscore the importance of vigilance and control measures to be undertaken by residents in their respective households.